2022
DOI: 10.1021/acs.jpcb.2c03389
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium Effects of Polymer Dynamics under Nanometer Confinement: Effects of Architecture and Molar Mass

Abstract: The non-equilibrium dynamics of linear and star-shaped cis-1,4 polyisoprenes confined within nanoporous alumina is explored as a function of pore size, d, molar mass, and functionality (f = 2, 6, and 64). Two thermal protocols are tested: one resembling a quasi-static process (I) and another involving fast cooling followed by annealing (II). Although both protocols give identical equilibrium times, it is through protocol I that it is easier to extract the equilibrium times, t eq, by the linear relationships of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 51 publications
(93 reference statements)
3
17
0
Order By: Relevance
“…Notably, the above described long-time reorganization process of the cPB/alumina interface effects, at temperatures well above the bulk T g (here at about T g + 235 K ), occurs within characteristic times of, at least, several μs, more than 3 orders of magnitude above the maximum (end to end vector) relaxation time of cPB chains in bulk, which, at the same thermodynamic conditions, is about τ end bulk = 2.95 ns. Such long-time re-organization phenomena of the cPB/alumina interfacial (or bound) layer are in agreement with recent experimental studies regarding the conformational equilibration of polymers, at the vicinity of, especially, strongly attractive interfaces, that may require hours or even days, very far from the accessible time window of current atomistic MD simulation methods. , …”
Section: Structure Of the Bound Layer At The Pb/alumina Interfacesupporting
confidence: 89%
“…Notably, the above described long-time reorganization process of the cPB/alumina interface effects, at temperatures well above the bulk T g (here at about T g + 235 K ), occurs within characteristic times of, at least, several μs, more than 3 orders of magnitude above the maximum (end to end vector) relaxation time of cPB chains in bulk, which, at the same thermodynamic conditions, is about τ end bulk = 2.95 ns. Such long-time re-organization phenomena of the cPB/alumina interfacial (or bound) layer are in agreement with recent experimental studies regarding the conformational equilibration of polymers, at the vicinity of, especially, strongly attractive interfaces, that may require hours or even days, very far from the accessible time window of current atomistic MD simulation methods. , …”
Section: Structure Of the Bound Layer At The Pb/alumina Interfacesupporting
confidence: 89%
“…This leads to a result that most of the chains run parallel through the capillary in an approximately straight state, as has been observed in semidilute solutions . Such chain orientation effects have recently being discussed for the segmental and chain process of cis -1,4-polyisoprene confined in nanoporous aluminum . The combination of the chain orientation and the decrease in average number of entanglement points Z per chain provide further evidence in support of the theory that chains can only move along the “reptation tube” under confinement.…”
Section: Resultssupporting
confidence: 54%
“…50 Such chain orientation effects have recently being discussed for the segmental and chain process of cis-1,4polyisoprene confined in nanoporous aluminum. 51 The combination of the chain orientation and the decrease in average number of entanglement points Z per chain provide further evidence in support of the theory that chains can only move along the "reptation tube" under confinement. Considering all effects together, we calculate the effective viscosity η eff from the LWE as η eff = γR cos θ/2A a 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 57%
“…As reported in the majority of cases, the prolonged annealing of glass formers at nanoscale confinement results in continuous changes, reflected in retardation of structural/segmental dynamics due to a variation in the density packing at the interface that is transferred to the “core” molecules (of more bulklike dynamics). Interestingly, for some materials, it was even possible to recover the bulklike characteristics with annealing. ,, This time-induced variation of the molecular dynamics was assigned to the adsorption–desorption process (leading to the reduction of free volume at the interface) , or, alternatively (additionally), to a “mass exchange” between the interfacial fraction and those molecules located at some distance from the surface. ,,, Note that the rearrangement of confinement-induced molecular conformations might also contribute to the mentioned phenomenon. Recently, it was postulated that, in the case of liquids infiltrated into mesopores, this process is strictly driven by the vitrified interfacial layer, whereas the equilibration time scale correlates with the viscous flow under confinement and also depends on the pores’ morphology (including their finite size and functionality) . Herein, one can mention the studies on thin polymer films, which also indicated that the rate of the equilibration process of macromolecules under confinement is governed by the dynamics of polymer chains, which are irreversibly adsorbed at the interface .…”
mentioning
confidence: 99%
“…Recently, it was postulated that, in the case of liquids infiltrated into mesopores, this process is strictly driven by the vitrified interfacial layer, whereas the equilibration time scale correlates with the viscous flow under confinement 43 and also depends on the pores’ morphology (including their finite size and functionality). 48 Herein, one can mention the studies on thin polymer films, which also indicated that the rate of the equilibration process of macromolecules under confinement is governed by the dynamics of polymer chains, which are irreversibly adsorbed at the interface. 49 Importantly, aside from the density fluctuations, Song et al 50 also showed that the slow mode (SAP) appearing in the loss spectra collected for the polymeric thin films may drive glasses toward equilibrium.…”
mentioning
confidence: 99%